THE ROLE OF MAGNESIUM SUPPLEMENTS ON HYPERTENSION IN PREGNANCY AND PREECLAMPSIA - Nurwany, Raissa; Ramadhina, Shafira Fitri; Pariyana, Pariyana (Andalas Obstetrics And Gynecology Journal, 2024)
Objective:This article aims to discuss the effects of magnesium supplementation on clinical outcomes of pregnancy and highlights the benefits of magnesium supplementation in reducing the risk of hypertension in pregnancy and preeclampsia. Method: In this systematic review article, the author conducted a literature search using certain keywords and selected articles that were published from 2013-2023, can be accessed in full-text in pdf format, and are in Indonesian or English. The methods used were in accordance with the reporting guidelines provided in the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P). Results: After carefully searching the database and eliminating articles that were not related to the topic, 6 articles were obtained for review. Hypertension in pregnancy and preeclampsia are serious health problems that can harm both mother and baby. Magnesium supplements have been studied as a way to reduce the risk of hypertension in pregnancy and preeclampsia. Conclusion: Magnesium supplements may help reduce the risk of hypertension in pregnancy and preeclampsia.